2013
DOI: 10.7557/2.33.1.2598
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental effects affecting the variation in birth date and birth weight of reindeer calves

Abstract: e factors causing variation in birth date and birth weight were analysed from the data from an experimental reindeer herd consisting of 1136 calves with parental information. e traits had coe cient of variation of 37 and 14%, respectively. e variation in both traits was a ected by year and sex (male calves heavier) and by management factors, such as the age distribution of females and males. Early calving results from the use of older breeding males and is most apparent in prime age females. In both traits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
(47 reference statements)
4
9
0
Order By: Relevance
“…Heydarpour et al, 2008). Contrary to the birth weight of reindeer (Muuttoranta et al, 2013), the inclusion of the maternal e ect in the growth model did not cause reduction in the direct heritability, as also reported by Safari et al (2005) for sheep. In reindeer this is due to the strongly negative direct-maternal genetic correlation in growth (Willham, 1972; Table 2).…”
Section: Genetic Variationmentioning
confidence: 49%
See 2 more Smart Citations
“…Heydarpour et al, 2008). Contrary to the birth weight of reindeer (Muuttoranta et al, 2013), the inclusion of the maternal e ect in the growth model did not cause reduction in the direct heritability, as also reported by Safari et al (2005) for sheep. In reindeer this is due to the strongly negative direct-maternal genetic correlation in growth (Willham, 1972; Table 2).…”
Section: Genetic Variationmentioning
confidence: 49%
“…In addition, paternities were monitored using marking harnesses for calves born in 1987, 1988, and 1990-1993. e pedigree dataset contained 3320 animals, of which 101 were sires and 566 dams of the calves. e dataset has been described in Muuttoranta et al (2013) Calf data e calves were weighed at birth in May (few born in June) and before selection in September. e weights are in kilograms and birth date is presented as days counting from 1 st of May.…”
Section: Data Description and Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heritability estimated for birth date and calf body mass were of the same order as previously recorded in reindeer (both traits, Muuttoranta et al, 2013), Feder et al, 2008), soay sheep Ovis aries (both traits, Wilson et al, 2005a) and red deer (body mass, Kruuk and Hadfield, 2007). Our sample sizes of less than 170 individuals (see Table 2) limited the quantitative genetic analyses to univariate models (Kruuk, 2004;de Villemereuil et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
“…Hence, the unmeasured additive genetic covariance could have limited the additive genetic variation in each trait that was available for unconstrained phenotypic evolution (Hansen and Houle, 2008;. Indeed, a negative genetic covariance between birth mass and date has earlier been found for instance in reindeer (Muuttoranta et al, 2013), while a positive genetic covariance has been found in soay sheep (Wilson et al, 2005a). Although we were not able to estimate genetic covariances in this study, we found a negative phenotypic covariance between calf body mass and birth date, which could indicate the presence of a negative genetic covariance (see Table 2; Cheverud, 1988).…”
Section: Discussionmentioning
confidence: 99%